Text Message-Based Intervention Targeting Alcohol Consumption Among University Students: Findings From a Formative Development Study - Thomas, Kristin (JMIR Mhealth Uhealth, 2016)
BACKGROUND: Drinking of alcohol among university students is a global phenomenon; heavy episodic drinking is accepted despite several potential negative consequences. There is emerging evidence that short message service (SMS) text messaging interventions are effective to promote behavior change among students. However, it is still unclear how effectiveness can be optimized through intervention design or how user interest and adherence can be maximized. OBJECTIVE: The objective of this study was to develop an SMS text message-based intervention targeting alcohol drinking among university students using formative research. METHODS: A formative research design was used including an iterative revision process based on input from end users and experts. Data were collected via seven focus groups with students and a panel evaluation involving students (n=15) and experts (n=5). Student participants were recruited from five universities in Sweden. A semistructured interview guide was used in the focus groups and included questions on alcohol culture, message content, and intervention format. The panel evaluation asked participants to rate to what degree preliminary messages were understandable, usable, and had a good tone on a scale from 1 (very low degree) to 4 (very high degree). Participants could also write their own comments for each message. Qualitative data were analyzed using qualitative descriptive analysis. Quantitative data were analyzed using descriptive statistics. The SMS text messages and the intervention format were revised continuously in parallel with data collection. A behavior change technique (BCT) analysis was conducted on the final version of the program. RESULTS: Overall, students were positive toward the SMS text message intervention. Messages that were neutral, motivated, clear, and tangible engaged students. Students expressed that they preferred short, concise messages and confirmed that a 6-week intervention was an appropriate duration. However, there was limited consensus regarding SMS text message frequency, personalization of messages, and timing. Overall, messages scored high on understanding (mean 3.86, SD 0.43), usability (mean 3.70, SD 0.61), and tone (mean 3.78, SD 0.53). Participants added comments to 67 of 70 messages, including suggestions for change in wording, order of messages, and feedback on why a message was unclear or needed major revision. Comments also included positive feedback that confirmed the value of the messages. Twenty-three BCTs aimed at addressing self-regulatory skills, for example, were identified in the final program. CONCLUSIONS: The formative research design was valuable and resulted in significant changes to the intervention. All the original SMS text messages were changed and new messages were added. Overall, the findings showed that students were positive toward receiving support through SMS text message and that neutral, motivated, clear, and tangible messages promoted engagement. However, limited consensus was found on the timing, frequency, and tailoring of messages.